Response to Aflibercept Therapy in Three Types of Choroidal Neovascular Membrane in Neovascular Age-Related Macular Degeneration: Real-Life Evidence in the Czech Republic. (10th June 2019) - Nemcansky, Jan; Stepanov, Alexandr; Koubek, Michal; Veith, Miroslav; Klimesova, Yun Min; Studnicka, Jan
Abstract : Purpose . To present a cohort of treatment-naive patients with the neovascular form of age-related macular degeneration (nAMD) treated with aflibercept in a fixed regimen and evaluate the treatment response of three types of choroidal neovascular membrane (CNV)—occult (Type 1), classic (Type 2), and minimally classic (Type 4). Methods . This was a multicentre, prospective, observational consecutive case series study. Patients diagnosed with three types of CNV of nAMD were treated in a fixed regimen (3 injections every 4 weeks, and then injections at 8 week intervals). The follow-up period was 48 weeks. Best-corrected visual acuity (BCVA) and central retinal thickness (CRT) were measured using Early Treatment Diabetic Retinopathy Study (ETDRS) charts and spectral-domain optical coherence tomography (OCT). The measurements were taken at the baseline and then at 16, 32, and 48 weeks. Results . The treatment-naive group was composed of 135 eyes of 135 patients in the study. 61 eyes had Type 1 lesions of CNV, 50 eyes had Type 2 lesions, and 24 eyes had Type 4 lesions. Mean baseline BCVA ± SD for Type 1 lesions was 56.1 ± 10.8 ETDRS letters, and then 62.2 ± 12.9 letters, 61.2 ± 13.7 letters, and 62.8 ± 15.1 letters at 16, 32, and 48 weeks, respectively. Mean baseline CRT ± SD for Type 1 lesions was 442.4 ± 194.9 μ m, and then 302.5 ± 144.4 μ m, 299.7 ± 128.5 μ m, and 277.7 ± 106.5 μ m at 16, 32, and 48 weeks, respectively. Mean baseline BCVA ± SD for Type 2 lesions was 55.6 ± 9.9 ETDRS letters, and then 62.5 ± 11.1 letters, 60.7 ± 13.0 letters, and 62.5 ± 14.2 letters at 16, 32, and 48 weeks, respectively. Mean baseline CRT ± SD. For Type 4 lesions mean baseline BCVA ± SD was 56.7 ± 9.0 ETDRS letters, and then 59.1 ± 10.6 letters, 59.5 ± 11.4 letters, and 59.2 ± 12.6 letters at 16, 32, and 48 weeks respectively. Mean baseline CRT ± SD for Type 4 lesions was 492.1 ± 187.0 μ m, and then 333.3 ± 137.5 μ m, 354.4 ± 175.0 μ m, and 326.7 ± 122.4 μ m at 16, 32, and 48 weeks respectively. All these changes were statistically significant (p < 0.005 ). Conclusions . The primary outcome of our study is that the treatment with aflibercept in nAMD patients led to statistically significant improvement in BCVA and to a decrease in CRT throughout the follow-up period in both occult and classic types of CNV. The minimally classic type of CNV demonstrated a poorer functional and anatomical response to treatment.